Materiais com estrutura perovskita : síntese e aplicação na adsorção em fase líquida - Leite, Jamila Oliveira (2017)
Researchers are still making major efforts to obtain active, selective and high surface area. Perovskite-type catalysts have gained prominence in recent years, as they have properties that allow their wide use in various catalytic reactions and in the adsorption area, because their materials are easy to obtain and they have a low cost. Studies that enable the parameters identification that help to improve, in improving these potentialities, become paramount and of great value, mainly for the environmental application. In this regard, this paper was developed with the objective of obtaining oxides with perovskite structure based on nickel for later evaluation of its evaluation of the dye removal ability in solution. The adsorbent LaNiO3 was prepared by the collagen-modified protein method and the adsorbents LaNiO3/Al2O3 and LaNiO3 /TiO2 were prepared by impregnation with excess solvent. The samples were analyzed by TG / DTG, FTIR, XRD analyzed the samples by powder method, ASE and TPR. The TG/ DTG analysis allowed the identification of the best calcination temperature to obtain the perovskite. The FTIR results of the LNC350 sample showed bands attributed to the characteristic groups of the complexing agent, suggesting a possible coordination of the present metals. The X-ray diffractograms of the LNC900, LNC900/Al and LNC900/Ti samples proved the formation and maintenance of the crystalline phase of the perovskites in the presence of the alumina and titania supports. The supports promoted an increase in the total area in relation to the mass sample. The results of the TPR analysis were able to show the reduction zones, characteristic of LaNiO3 type materials. The kinetic and equilibrium adsorption studies enabled the evaluation of the adsorbate interaction on the surface of the adsorbent.